Assessment of molecular and morphological dynamics during long-time in vitro cultivation of cryopreserved human ovarian tissue: risk of genetic alterations - Wang, Wanxue; Todorov, Plamen; Isachenko, Evgenia; Rahimi, Gohar; Merzenich, Markus; Mallmann-Gottschalk, Nina; Zhou, Yang; Yao, Jilong; Li, Xuemei; Isachenko, Volodimir (Frontiers in Endocrinology, 2025)
Background: Cryopreservation of human ovarian tissue is a technology for patients undergoing aggressive anticancer treatments. This technology includes the following stages: saturation by permeable cryoprotectants, freezing, thawing, removal of cryoprotectants, as well as tissues in vitro or in situ culture. Objective: Evaluation of quality of tissue after cryopreservation and in vitro culture with the aim of detection of genetic and molecular changes in cells. Methods: Ovarian tissue was frozen in 6% ethylene glycol and 6% dimethyl sulfoxide with speed of cooling 0.3°C/min and thawed at 100°C. After removal of cryoprotectants tissue fragments were in vitro cultured with the soluble extract of basement membrane protein (Matrigel) 3-D culture system for 7 days. Morphological and functional assessments were conducted using microscopic observation and RNA-Sequencing. Comparative analysis of tissue morphology before and after culture was performed with bioinformatics for gene expression and variant analysis, including functional annotation and study of protein-protein interaction. Results: DNA and RNA analyses after cultivation indicated a rise in gene fusion and alternative splicing events, potentially affecting gene expression and cellular functions. Conclusion: longtime in vitro culture of human ovarian tissue results in substantial changes in its morphology and genetic alteration.